The Form and Function of Antan Delapan Music in Muara Lawai Village, Muara Enim District - Aghnini, Aghnini; Sunarto, Sunarto; Triyanto, Triyanto (Catharsis, 2020)
Antan Delapan music is one of the arts found in the district of Muara Enim, South Sumatra. Antan Delapan art is currently displaced by the development of western music, therefore the form and function of music plays an important role in maintaining the Antan Delapan music among the people of Muara Enim Regency. The purpose is to study the form and function of Antan Delapan music. The method in this study uses descriptive qualitative with an interdisciplinary approach, while the data collection technique uses observation, interviews, and document studies. The data validity technique uses source triangulation. Data analysis techniques use the concepts of Strauss and Corbic. The results of this study are the form of Antan Delapan music which is dissected through the elements of time, melody, harmony, while the function of Antan Delapan music in the community as, entertainment, aesthetic appreciation, means of communication, cultural harmony, and as an integration. And it is hoped that this research can be useful for the people of Muara Enim Regency, especially the Muare Lawai Village Community in order to know the function and form of Antan Delapan music and can maintain the Antan Delapan music among the Muare Lawai villagers, and is useful for readers who will use music theory about the form and music function.